High-quality reference genome sequences of two Cannaceae species provide insights into the evolution of Cannaceae - Fu, Yuhua; Jiang, Sirong; Zou, Meiling; Xiao, Jianjia; Yang, Long; Luo, Chunfang; Rao, Ping; Wang, Wenquan; Ou, Zhengui; Liu, Fanzhi; Xia, Zhiqiang (Frontiers in Plant Science, 2022)
Canna edulis Ker-Gawl and Canna indica L. are species belonging to the Cannaceae family and both have a very high economic value. Here, we aimed to assemble genomes of C. edulis and C. indica at the chromosome level to generate a reference genome for the Cannaceae family. We also comparatively analyzed the genomes of C. edulis and C. indica and examined the molecular mechanisms responsible for the remarkable differences in plant characteristics in C. edulis varieties. Our results indicated that genome-wide duplication events had recently occurred in C. edulis and C. indica. The comparative analysis of the genomes of C. edulis and C. indica revealed that C. edulis exhibited a remarkable level of replication of genes in the starch and sucrose metabolic pathways, especially during sucrose hydrolysis. This finding is consistent with the fact that the starch content of the C. edulis tuber is higher than that of C. indica. Simplified genome re-sequencing revealed the population structure of 241 C. edulis genes, and a genome-wide association study of leaf traits revealed the location of key genes related to leaf color and morphology. These findings extend our understanding of Cannaceade at the molecular level, and provide an effective theoretical basis for further study and utilization of Cannaceae plants.